Influence of sociodemographic and emotional factors on the relationship between self-compassion and perceived stress among men residing in Brazil during the COVID-19 pandemic - Palma, Emanuel Missias Silva (2022)
The analysis of sociodemographic and emotional factors is essential to understanding how men perceive stress and practice self-compassion. In health crises, this problem becomes an emergency for public health. This study aimed to analyze the influence of sociodemographic and emotional factors on the relationship between self-compassion and the perceived stress of men residing in Brazil during the COVID-19 pandemic. This is a nationwide cross-sectional study carried out between June and December 2020 with 1006 men who completed a semi-structured electronic questionnaire. Data were collected using the snowball technique. Perceived stress was measured by the Perceived Stress Scale (PSS-14), and self-compassion was assessed using the Self-Compassion Scale. Most men had low self-compassion (51.5%; n = 516) and a moderate level of perceived stress (60.9%; n = 613), while 15.9% (n = 170) had a high level of stress. The prevalence of men in the combined situation of low self-compassion and high perceived stress was 39.4% (n = 334). Living with friends had a higher prevalence of low self-compassion and high perceived stress. The prevalence of common mental disorders was high (54.3%). Men with low levels of self-compassion reported higher levels of perceived stress; however, this association was moderated by emotional and sociodemographic variables. These findings highlight the importance of considering individual and contextual factors in public policies promoting men’s mental health.